The case of the disappearing librarians: analyzing documentation of librarians’ contributions to systematic reviews - Amelia Brunskill; Rosie Hanneke (Journal of the Medical Library Association, 2023)
Objective: The study aimed to analyze the documented role of a librarian in published systematic reviews and meta-analyses whose registered protocols mentioned librarian involvement. The intention was to identify how, or if, librarians’ involvement was formally documented, how their contributions were described, and if there were any potential connections between this documentation and basic metrics of search reproducibility and quality.